PENERAPAN MODEL PEMBELAJARAN STRUCTURE NUMBERED HEADS MATERI OPERASI HITUNG BILANGAN PECAHAN MTs AL–FATHAANAH MEMPAWAH HILIR - Nopita Sari; Agung Hartoyo; Dede Suratman (Jurnal AlphaEuclidEdu, 2021)
In the study effectiveness is very important, learning is said to b e successful when learners and educators can achieve the objectives to be reached. The effectiveness of what this researchsats is the learning activities performed by the teacher in administering the materials to be presented, the study activity, and the learning result of the learners. The purpose of the researchto see the effectiveness of these three aspects in applying the research Structure Numbered Heads to the operating material VII MTs. Al-Fataanah Memapawah Hilir. The method used in research is experimental method, with the shape of the research is a One- Shot  Case Study. The subjects in this study are VII-A class learners and  teachers at MTs. Al-Fataanah Mempawah Hilir. Research data is obtained from the administration of study tests (posttest), the learning management observation sheet and the observation sheet of participants activities. The result of all three learning effectiveness is that the learning  process applies 3,04 cooperative types of Structure Numbered Heads to good categories, learning activity percentage is 68,9% in the active category, learners can achieve the greatest learning result of individual achievement of  8 or 40% and classified intellgence is not lade. Since there is an unfulfilled indicator that the achievement of classified learning will not be achieved it seems that the study of applying cooperative models Structure Numbered Heads is not effective to apply in program  class  MTs. Al-Fataanah  Mempawah Hilir.